Effectiveness of Locally Available Superplasticizers on the Workability and Strength of Concrete - Ashfaque Ahmed Jhatial; Samiullah Sohu; Muhammad Tahir Lakhiar; Jam Shahzaib; Ahsan Ali Buriro (Civil Engineering Journal, 2018)
Though superplasticizers (SP) are well-known chemical admixtures which are added into concrete to enhance the workability and achieve higher strength while reducing the water content. But the rapid increase in different SP in Pakistan has created confusion on the effectiveness of SP. This experimental study was carried out to study the effect of locally available SP on the workability and compressive strength of M15 grade concrete. Three different SP were utilized, with dosage ranging from 0.5% to 2.5% with an increment of 0.5%. The water-cement ratio remained constant at 0.5 for all samples. Based upon the results, all three SP increased the workability as well as strength of concrete. The optimum dosage was determined to be 1.5% to 2.00% for all three SPs used in this research work. BASF 561 was determined to be more effective, as it achieved the maximum workability as well as compressive and flexural strengths.